Ιστορίες πρόσληψης έργων της Κρητικής Αναγέννησης. Ο Byron και η Βοσκοπούλα: Η διαιώνιση μιας παρεξήγησης - Κατσιγιάννης Αλέξανδρος (The Gleaner, 2011)
BYRON AND THE RECEPTION OF THE CRETAN PASTORAL POEM VOSKOPOULA The Prolonging of a Misunderstanding In this essay I will discuss whether Byron was indeed influenced by the Cretan pastoral poem Voskopoula in some cantos of his epic-satiric poem Don Juan (published in 1819), as argued by D.C. Hesseling in 1938 and by several researchers after him. This discussion stands as a starting point to analysing the reception of the literary works of the Cretan Renaissance by English scholars in the first two decades of the 19th century. In parallel, I hope that this article will shed light upon the troubling matter of the popular reception of Cretan Renaissance poetry and demotic songs by the scholars of the Enlightenment and Romanticism, which led to several misunderstandings concerning the character, origin and dissemination of Cretan Renaissance poetry in the scholars’ discourse network throughout the 19th century. ALEXANDER KATSIGIANNIS